2020
DOI: 10.1126/science.aax6874
|View full text |Cite
|
Sign up to set email alerts
|

Decay of the coronal magnetic field can release sufficient energy to power a solar flare

Abstract: Solar flares are powered by a rapid release of energy in the solar corona, thought to be produced by the decay of the coronal magnetic field strength. Direct quantitative measurements of the evolving magnetic field strength are required to test this. We report microwave observations of a solar flare, showing spatial and temporal changes in the coronal magnetic field. The field decays at a rate of ~5 Gauss per second for 2 minutes, as measured within a flare subvolume of ~1028 cubic centimeters. This fast rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
124
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(146 citation statements)
references
References 32 publications
13
124
2
7
Order By: Relevance
“…In spite of all the complications, modeling of individual flares (e.g., Nindos et al, 2000b;Kundu et al, 2004a;Tzatzakis et al, 2008;Gary et al, 2013Gary et al, , 2018Kuznetsov and Kontar, 2015;Fleishman et al, 2016bFleishman et al, ,c, 2018Kuroda et al, 2018) showed that the magnetic field may lie from less than 200 G (loop top) to about 1700 G (footpoints). Probably the most spectacular result was obtained by Fleishman et al (2020) who modeled spectroscopic imaging observations from Expanded OVSA (EOVSA) and found that the magnetic field decayed at a rate of about 5 G s −1 for 2 min.…”
Section: Gyrosynchrotron Emission From Model Flaring Loopsmentioning
confidence: 99%
“…In spite of all the complications, modeling of individual flares (e.g., Nindos et al, 2000b;Kundu et al, 2004a;Tzatzakis et al, 2008;Gary et al, 2013Gary et al, , 2018Kuznetsov and Kontar, 2015;Fleishman et al, 2016bFleishman et al, ,c, 2018Kuroda et al, 2018) showed that the magnetic field may lie from less than 200 G (loop top) to about 1700 G (footpoints). Probably the most spectacular result was obtained by Fleishman et al (2020) who modeled spectroscopic imaging observations from Expanded OVSA (EOVSA) and found that the magnetic field decayed at a rate of about 5 G s −1 for 2 min.…”
Section: Gyrosynchrotron Emission From Model Flaring Loopsmentioning
confidence: 99%
“…Observations of shocks driven by solar eruptions can also be used to infer coronal magnetic field strengths along the shock paths (e.g., 10,11), but such shocks are only occasionally observed. Radio observations have also been used to estimate the coronal magnetic field, but only in localized regions (e.g., 12,13); this method requires accurate identification of the radio emission mechanisms, which are not always clear. Due to the observational difficulties with each of these methods, no routine measurements of the global coronal magnetic field are available.…”
Section: Main Textmentioning
confidence: 99%
“…Radio spectral observations of type III bursts, spike structures associated with type IV bursts and zebra patterns could also provide estimates of the magnetic field in the coronal source regions of the radio emission [21][22][23]. In addition, when the emission mechanisms are known, microwave imaging at one or more frequencies could be used to produce maps of the coronal magnetic field strength in limited regions [24][25][26][27][28][29]. More recently, the phenomenon of magnetic-fieldinduced transition (MIT) [30] has caught the attention of the solar physics community, and theoretical and laboratory investigations have demonstrated the potential of MIT lines in measurements of the coronal magnetic field [31][32][33].…”
Section: Introductionmentioning
confidence: 99%